2022
DOI: 10.3390/app12041915
|View full text |Cite
|
Sign up to set email alerts
|

Composition of the Wild Rabbit Nest and Its Implication for Domestic Rabbit Breeding

Abstract: Wild European rabbits (Oryctolagus cuniculus) give birth in an underground nursery burrow where the kits are hermetically closed into the nest chamber for several weeks except for the three minutes of daily nursing. Given this confinement, the nest quality seems to be crucial in affecting the kits’ survival. The situation is less critical in rabbitries where the domesticated descendants are kept and give birth in separate nest boxes where the temperature and humidity conditions are less extreme and nests consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 56 publications
0
3
0
Order By: Relevance
“…The thermal insulation capacity of the nest depends largely on the structure of the nest-building material [36,37]. Materials with a fibrous structure proved to be better for creating the appropriate nest shape for rabbits [34] and mice [38], where the animals preferred materials used in nature. After hay, paper nesting material was preferred by ground squirrels over Lignocel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The thermal insulation capacity of the nest depends largely on the structure of the nest-building material [36,37]. Materials with a fibrous structure proved to be better for creating the appropriate nest shape for rabbits [34] and mice [38], where the animals preferred materials used in nature. After hay, paper nesting material was preferred by ground squirrels over Lignocel.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of the nests was examined based on the studies of Szenczi et al [33] and Bilkó et al [34]. We determined the composition of the materials used for the completed nests by the end of the seventh day by pulling out 20 threads haphazardly from the completed nests and homogenising them.…”
Section: Nest Materials Selection Testmentioning
confidence: 99%
“…A nest is constructed using vegetation collected from outside but is lined with fur plucked from the female's belly [44]. Bilkó et al [45] showed that rabbit nests were 43% fur and 55% plant material, which was almost entirely long dry grass (rather than fresh grass) of various species. In addition, brush-tailed phascogales ( Phascogale tapoatafa , Dasyuridae) of Australia build elaborate maternity nests in nest-boxes that are made of soft bark strips interwoven with feathers and fur [46].…”
Section: Materials Used In Nest Constructionmentioning
confidence: 99%